A three-miRNA panel in serum as a noninvasive biomarker for colorectal cancer detection. Issue 3 (September 2020) - Peng, Xiqi; Wang, Jingyao; Zhang, Chunduo; Liu, Kaihao; Zhao, Liwen; Chen, Xuan; Huang, Guocheng; Lai, Yongqing
Background: Circulating miRNAs have been proved to be promising biomarkers for disease detection in recent years. The present study aimed at exploring available serum miRNA biomarkers for the detection of colorectal cancer. Methods: A three-phase study was performed to select and validate candidate miRNAs with significant dysregulation in colorectal cancer using quantitative reverse transcription-polymerase chain reaction. This study recruited 137 colorectal cancer patients and 145 healthy controls. The diagnostic values of miRNAs were evaluated by receiver operating characteristic analysis. Bioinformatics analyses were utilized to predict target genes of miRNAs, and to conduct functional annotation and enrichment. Results: miR-30e-3p, miR-31-5p, miR-34b-3p and miR-146a-5p, miR-148a-3p and miR-192-5p were significantly dysregulated in colorectal cancer serum when compared with healthy controls. The panel composed of miR-30e-3p, miR-146a-5p, and miR-148a-3p exhibited strong diagnostic ability. The area under the receiver operating characteristic curve of the three-miRNA panel was 0.883, with a sensitivity of 0.800 and specificity of 0.787. Conclusion: The present study identified a three-miRNA panel in serum with a strong diagnostic ability of colorectal cancer, which may be able to serve as a novel noninvasive biomarker for colorectal cancer detection.